2020
DOI: 10.1021/jasms.0c00440
|View full text |Cite
|
Sign up to set email alerts
|

Linkage Memory in Underivatized Protonated Carbohydrates

Abstract: Carbohydrates are among the most complex class of biomolecules, and even subtle variations in their structures are attributed to diverse biological functions. Mass spectrometry has been essential for large scale glycomics and glycoproteomics studies, but the gas-phase structures and sometimes anomalous fragmentation properties of carbohydrates present longstanding challenges. Here we investigate the gas-phase properties of a panel of isomeric protonated disaccharides differing in their linkage configurations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Previous literature reports have shown that Fuc­(α1,2)­Gal­(β1,4)­Glc and Gal­(β1,4)-[Fuc­(α1,3)]-Glc could not be resolved from one another with a homebuilt 2 m DT IMS–MS platform but did have diagnostic cryogenic IR fingerprints. Another recent study on the three fucosylglucosamine isomers showed that subtle differences were present in their arrival time distributions as their [M – H 2 O + H] + adducts on a 25 cm TWIMS–MS platform but were not analyzed, or resolved, as an isomeric mixture. By utilizing the novel capabilities of the cIMS array, we were able to slice out selected mobility regions and subject them to additional cycles, thus enabling the resolution of these challenging fucose-containing HMO building block isomers.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Previous literature reports have shown that Fuc­(α1,2)­Gal­(β1,4)­Glc and Gal­(β1,4)-[Fuc­(α1,3)]-Glc could not be resolved from one another with a homebuilt 2 m DT IMS–MS platform but did have diagnostic cryogenic IR fingerprints. Another recent study on the three fucosylglucosamine isomers showed that subtle differences were present in their arrival time distributions as their [M – H 2 O + H] + adducts on a 25 cm TWIMS–MS platform but were not analyzed, or resolved, as an isomeric mixture. By utilizing the novel capabilities of the cIMS array, we were able to slice out selected mobility regions and subject them to additional cycles, thus enabling the resolution of these challenging fucose-containing HMO building block isomers.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Glycosidic cleavage yields information about glycan sequence, whereas cross-ring cleavage is important to deduce information about linkage and branching. Glycosidic B-fragments are also particularly interesting for chemical synthesis of glycans as they are believed to occur as intermediates of S N 1 reactions in solution, and their reactivity can be predicted by gas-phase studies. , Glycosidic B- and C-fragments showed in some cases a memory of the stereoinformation on the glycosidic linkage in unprotected glycosides but not in protected glycosides …”
Section: Techniquesmentioning
confidence: 99%
“…Ion mobility spectrometry (IMS), a technique in which gas-phase ions are separated based on their collisional cross section with an inert buffer gas, has been combined with MS n to provide a rapid and effective tool for glycan analysis. Such studies in which fragments generated by collision-induced dissociation (CID) are characterized by IMS have led to the identification of regioisomers and anomers of the precursor glycans. , Ultrahigh-resolution IMS has been able to separate subtle substructures in small glycans, and a cyclic IMS instrument has recently been used to separate and partially identify the isomers of a set of pentasaccharides based on their fragmentation pattern. , However, the ever-increasing resolution of IMS devices leads to the observation of multiple peaks in the arrival-time distribution (ATD). This complicates the interpretation of IMS data, as the separated reducing-end anomers, which are in equilibrium in solution, can then be confused with other structures such as positional isomers, regioisomers, or conformers.…”
Section: Introductionmentioning
confidence: 99%